2005
DOI: 10.2106/jbjs.d.02003
|View full text |Cite
|
Sign up to set email alerts
|

Interscalene Regional Anesthesia for Shoulder Surgery

Abstract: Interscalene regional block provides effective anesthesia for most types of shoulder surgery, including arthroplasty and fracture fixation. When administered by an anesthesiologist committed to and skilled in the technique, the block has an excellent rate of success and is associated with a relatively low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
4
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 13 publications
1
62
4
1
Order By: Relevance
“…Furthermore, it is important to remember that IBPB is an invasive procedure that may lead to serious complications [3][4][5][6][7] including the common risks associated with peripheral nerve block (nerve damage, local anaesthetic toxicity), risk of pleural puncture and devastating complication as cervical spinal cord damage and permanent paralysis and it should be performed by practitioners with appropriate experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is important to remember that IBPB is an invasive procedure that may lead to serious complications [3][4][5][6][7] including the common risks associated with peripheral nerve block (nerve damage, local anaesthetic toxicity), risk of pleural puncture and devastating complication as cervical spinal cord damage and permanent paralysis and it should be performed by practitioners with appropriate experience.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it can be associated with severe acute adverse effects that are potentially devastating in addition to complications involving the peripheral nervous system [4,5]. These latter events, even if reported to a lesser degree, are evident when large case studies are examined, and can lead to a high level of patient discomfort that may interfere with postoperative assessment and function [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The length and type of surgery should be a consideration as well. Bishop et al showed interscalene block to be an effective technique for both arthoscopic and open procedures [92]. However, appropriate consideration should be used before performing a regional technique in a healthy patient undergoing a relatively simple, minimally invasive surgery.…”
Section: Regional Vs Generalmentioning
confidence: 99%
“…Interscalene branchial plexus block has several advantages for patients undergoing shoulder surgery, including excellent anaesthesia, opioid-sparing effects, delayed onset of postoperative pain, shortened postanaesthesia stay and increased patient satisfaction. [1][2][3] Interscalene branchial plexus block via in-dwelling perineural catheter for continuous infusion has revolutionized the practice of acute pain management for shoulder surgery in the postoperative period, since it provides prolonged postoperative analgesia. 2 Spinal anaesthesia has similar advantages, including postoperative analgesia and opioid sparing in orthopaedic surgery.…”
Section: Introductionmentioning
confidence: 99%